SOLUSI DARI PROBLEMATIK PROSES PEMBELAJARAN SELAMA COVID-19 DI SMPI AL ISHLAH BUKITTINGGI - Risdoyok Risdoyok (Padma Sari: Jurnal Ilmu Pendidikan, 2022)
Learning is a very important instrument in the intellectual life of the nation. In order to develop the cognitive, psychomotor, and affective potential of students. To develop potentials which of course are supported by a comfortable learning atmosphere and full of maximum guidance as well. This research method uses an approach approach with data sourced from observation, interviews and documentation, while the analytical method used in this research is descriptive qualitative research. The results of this study indicate that the learning process has changed, indirectly indicating the dynamics of education in Indonesia is disrupted. Such as the learning process is transferred at their respective homes (online), Second; transformation of learning media based on Digital Media, namely: WhatsApp groups, Google class, Googleomes', Office 365, Third; systems, methods, learning evaluation adapted and, Fourth; It is the cooperation of teachers and parents that determines the success of today's education. If the collaboration between teachers and parents is carried out well, the success of their learning will be achieved. Because in terms of influence they are learning quite a lot at this time, so their level of focus is according to them. For this reason, there is a need for more roles from parents while studying from home. At least this needs to be considered by all educational institutions to create the intelligence of the nation's life in any situation.